Motorcycle helmet fixation status is more crucial than helmet type in providing protection to the head. Issue 11 (November 2016) - Ramli, Roszalina; Oxley, Jennie
Abstract: Introduction: In Malaysia, motorcyclists continue to outnumber other road users in injuries and deaths. The objective of this study was to determine the association between helmet fixation and helmet type with head injury and severity of head injury among Malaysian motorcyclists. Methods: The study design was a prospective cross-sectional study. The participants involved injured motorcyclists who were admitted in five selected hospitals in Klang Valley, Malaysia. Participants who sustained head injury were selected as the cases while those with injury below the neck (IBN) were selected as the controls. Questionnaire comprising motorcyclist, vehicle, helmet and crash factors was examined. Diagnoses of injuries were obtained from the participants' medical records. Results: The total subjects with head injuries were 404 while those with IBN were 235. Majority of the cases (76.2%) and controls (80.4%) wore the half-head and open-face helmets, followed by the tropical helmets (5.4% and 6.0% of the cases and controls, respectively). Full-face helmets were used by 1.2% of the cases and 4.7% of the controls. 5.7% of the cases and 6.0% of the controls did not wear a helmet. 32.7% of the cases and 77.4% of the controls had their helmets fixed. Motorcyclists with ejected helmets were five times as likely to sustain head injury [adjusted odds ratio, AOR 5.73 (95% CI 3.38–9.73)] and four times as likely to sustain severe head injury [AOR of 4.83 (95% CI 2.76–8.45)]. The half head and open face helmets had AOR of 0.24 (95% CI 0.10–0.56) for severe head injury when compared to motorcyclists who did not wear a helmet. Conclusion: Helmet fixation is more effective than helmet type in providing protection to the motorcyclists.